Toll-like receptors in hepatocellular carcinoma: potential novel targets for pharmacological intervention. (1st September 2016) - Zou, Hai; Wang, Wu-Ke; Liu, Yan-Long; Braddock, Martin; Zheng, Ming-Hua; Huang, Dong-Sheng
ABSTRACT: Introduction : Toll-like receptors (TLRs) are expressed by a wide variety of cell types including immune cells. They play a crucial role in the inflammatory and host defense response against microorganisms, and triggering TLRs can mediate the activation of innate immunity. Furthermore, research suggests that various TLRs may function differently on different tumor cells. The change in TLR activity may elicit an anti-tumor activity in hepatocellular carcinoma (HCC) cells and may serve as a novel therapeutic target for HCC therapy. Areas covered : This review discusses the role of the TLR family in HCC and the underlying signaling pathway of TLRs as a form of pattern recognition receptor in mediating inflammation and HCC immunity responses. Agonists and antagonists of TLRs, which render TLRs as potential therapeutic targets, activate downstream molecules, subsequently causing HCC cell survival. The proliferation or protection against the development of HCC is also described. Expert opinion : A series of studies have highlighted a crucial role of TLRs in HCC and consider TLR signaling pathways as potential therapeutic targets for HCC. However, the conclusions of these studies are in part paradoxical and controversial. Thus, it is necessary to extend further research to help determine the signaling pathways involved.